Sphere of Physical Education and Sports as a Business Object - Vladimirovich, Pochinkin Alexander; Alekseevna, Prodanova Natalia; Leonidovna, Dimitrov Irina; Vladimirovich, Viseiko Sergey; Anatolyevich, Zaitsev Valery; Nikolaevna, Pozdeeva Svetlana (International Journal of Psychosocial Rehabilitation, 2020)
The article reveals the features of the formation, organization and progress of managerial and economic relations of sports organizations of national and international scale with business. It shows the prospects for the development of these relations in the future. The formation of sports business as an economic category takes place in conditions of increasing monetization of sports activities in general. In the global economy, sport is considered as one of the progressive segments taking into account the growth of incomes and revenues of the industry. The sports industry is developing rapidly with the expansion of the conceptual apparatus, areas of activity, and the list of goods and services. Considering the feature of sports business, which consists in the positive effect related to human health, and its ability to make a profit, the process of formation and development, the study is of scientific interest.